2020
DOI: 10.1007/978-981-15-4745-4_74
|View full text |Cite
|
Sign up to set email alerts
|

Queueing Theory an Index Factor for Production Inventory Control in Automotive Industry—A Review

Abstract: In this paper, various approaches to inventory control within the automotive industry were reviewed using queueing theory. Different models used in past literature were stated and the model considered to be most effective in this review is dock management modeling. This model was used to analyze inventory control and how effectively automotive industries can minimize inventory by getting the component needed in the assembly line just in time, this helps to reduce additional costs for warehouse maintenance and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…Bananas often have a short shelf life and begin to degrade right after being picked. Over the past 20 years, the production of bananas has continuously expanded, to about over 117 million tonnes in 2019 compared to 70 million tonnes in 1999 [52]. Many tons of banana peel trash are produced every day at fruit markets and in home garbage due to the anaerobic digestion of biomass, which produces gases that upset the natural equilibrium of the air.…”
Section: Banana Peel (Ash)mentioning
confidence: 99%
See 1 more Smart Citation
“…Bananas often have a short shelf life and begin to degrade right after being picked. Over the past 20 years, the production of bananas has continuously expanded, to about over 117 million tonnes in 2019 compared to 70 million tonnes in 1999 [52]. Many tons of banana peel trash are produced every day at fruit markets and in home garbage due to the anaerobic digestion of biomass, which produces gases that upset the natural equilibrium of the air.…”
Section: Banana Peel (Ash)mentioning
confidence: 99%
“…The values in literature shows that banana peel will be more brittle (Average Silicon: PKS > banana peel > Date Seed) while banana peel will have more strength (Average potassium: banana peel > Date Seed > PKS). In a review of agrowaste as a sustainable source of carbon for steel reinforcing, Afolalu et al, [52], concluded that because agrowaste has a high carbon content, it should be taken into consideration by steel manufacturing businesses.…”
Section: Elemental Composition Of Selected Agro Waste (Date Seed Pks ...mentioning
confidence: 99%
“…Generally, events to be served immediately have very little chance [9]. Queuing is the process of waiting on a system to be served to ensure a reduction of waiting time with extra planning and investment by the company concerned [10], [11]. This queuing process is closely related to the arrival of a customer in a system, queuing if the queue cannot be served, being served, and finally leaving the facility after being served [12].…”
Section: Introductionmentioning
confidence: 99%
“…It mainly involves planning, organization, and supervision of the process of manufacturing, production or providing services. It is delivery-focused by nature, concerned with the efficient transformation of material inputs to outputs [3]. Due to increasingly complex business environments, companies are driven to continually enhance organizational performance, pushing decision-makers such as operation managers to increase the efficiency and effectiveness of production activities [1].…”
Section: Introductionmentioning
confidence: 99%